Potential Impact of Aedes Albopictus (Skuse,1894), an Arbovirus and Nematode Vector, on Human Public Health - António J. dos Santos Grácio; Maria Amélia Grácio (Journal of Public Health International, 2019)
A review outlines the ecology and public health implications of Aedes albopictus as a vector of arboviruses and nematodes. Surveillance and control strategies are discussed.
Keywords: Aedes Albopictus